2021
DOI: 10.48550/arxiv.2108.10485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Non-ideal Magnetohydrodynamic Simulations of Protoplanetary Disks with Outer Truncation

Haifeng Yang,
Xue-Ning Bai

Abstract: It has recently been established that the evolution of protoplanetary disks is primarily driven by magnetized disk winds, requiring large-scale magnetic flux threading the disks. The size of such disks is expected to shrink in time, as opposed to the conventional scenario of viscous expansion. We present the first global 2D non-ideal magnetohydrodynamic (MHD) simulations of protoplanetary disks that are truncated in the outer radius, aiming to understand the interaction of the disk with the interstellar enviro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Such observations show that some disks display a relatively high α 10 −3 −0.1 (35,36), compatible with measurements from non-ideal MHD disk simulations (34). Moreover, a recent study found that even in the magnetized wind-driven disk where the MRI is fully quenched, the magnetic torque can also drive the expansion of the gas in the outer disk region, analogous to the viscous spreading effect (37). This implies that our expanding disk scenario can be applicable for a broad range of circumstances.…”
Section: Discussionsupporting
confidence: 81%
“…Such observations show that some disks display a relatively high α 10 −3 −0.1 (35,36), compatible with measurements from non-ideal MHD disk simulations (34). Moreover, a recent study found that even in the magnetized wind-driven disk where the MRI is fully quenched, the magnetic torque can also drive the expansion of the gas in the outer disk region, analogous to the viscous spreading effect (37). This implies that our expanding disk scenario can be applicable for a broad range of circumstances.…”
Section: Discussionsupporting
confidence: 81%
“…Such observations show that some disks display a relatively high  ≳ 10 −3 − 0.1 (35,36), compatible with measurements from nonideal MHD disk simulations (34). Moreover, a recent study found that, even in the magnetized winddriven disk where the MRI is fully quenched, the magnetic torque can also drive the expansion of the gas in the outer disk region, analogous to the viscous spreading effect (37). This implies that our expanding disk scenario can be applicable for a broad range of circumstances.…”
Section: Discussionsupporting
confidence: 79%
“…In the alternative magneto-hydrodynamical (MHD) disk wind model, angular momentum is transported in the wind, moving vertically away from the disk (Blandford & Payne 1982;Ferreira 1997;Gressel et al 2015;Bai et al 2016). That behavior can result in a more radially compact gas density distribution (e.g., Lesur 2021;Yang & Bai 2021). Comparing disk sizes in a large sam-ple that spans a range of evolutionary stages could help differentiate between the two scenarios.…”
Section: Introductionmentioning
confidence: 99%